Legal Development and Globalization: Some Contemporary Issues in Indonesia and Global Context - Ridwan Arifin (Journal of Law and Legal Reform, 2020)
When there is society, there always law, ubi societas ibi ius, has been impressed us that society always changes everyday and it impacted to the law enforcement itself. The inability of the law to respond the rapid changes even disruptive changes in the society raises its own problems in one hand, and challenges in the other hands. At this third issue, Journal of Law & Legal Reform Volume 1 Issue 3 (April 2020) presents some articles both original research articles and review articles from various institution and country. At this issue, the editor team highlight the focus theme â€œLaw and Development in Disruptive Era (Indonesia and Global Context)â€ to give a high impression that this volume not only debating the contemporary issues concerning to legal development, but also the impact of law changes or law reform in the society itself.